The Loan Application with Land Certificate Guarantee - Edi Rahadini; Bambang Tri Bawono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
Certificates on land as collateral for one's debt, in fact, must be able to replace a debt. But in reality, the guarantee cannot be executed as a substitute for someone's debt. This writing using legal protection theory which is the protection of the dignity and worth, as well as the recognition of human rights owned by legal subjects based on general provisions from arbitrariness or as a collection of rules or rules that will be able to protect something else. That the discussion of the article focuses on: How to apply for a loan with a land certificate as collateral? The purpose of writing this journal is to find out how to apply for credit with land certificates as collateral. This study uses a normative juridical approach, with analytical descriptive specifications. Data obtained by literature study. The conclusions obtained from the writing are: collateral is the ability of the debtor to fulfill or pay off his debt to the creditor, which is carried out by holding certain objects of economic value as dependents on the loan or debt received by the debtor to his creditor. Indeed, a certificate can be used as collateral for a debt, but this cannot be done, because the debt agreement is not followed up with a mortgage agreement.